PENGARUH MENGUNYAH BUAH NANAS (ANANAS COMOSUS L.MERR) TERHADAP DEBRIS INDEKS PADA REMAJA DI PANTI ASUHAN BAKTI MULIA KAROMBASAN KOTA MANADO - Ni Made Yuliana; I Ketut Harapan; Yenny Lisbeth Siahaan; Jeineke Ellen Ratuela (Poltekkes Kemenkes Medan, 2026)
Dental and oral hygiene is the condition of the teeth in the oral cavity in a clean condition free from plaque and other dirt on the surface of the teeth such as dirt, tartar and food scraps. Debris is mud deposits consisting of food remains that stick to the surface of the teeth. Adolescence is a transition period between childhood and adulthood. Pineapple fruit has a high air and fiber content, which can clean the surface of the mouth and can work as a digestive system. The aim of this research was to determine the effect of chewing pineapple on the debris index. This research was conducted using a quasi-experimental method with a group pretest-posttest design (one group), to assess the effect of chewing pineapple on the debris index. The research took place in May 2024. The total population was 36 respondents using a sampling technique, namely the total population technique. The data obtained was tabulated and analyzed using the Wilcoxon test because the data was not normally distributed. This research instrument uses diagnostic tools and a debris index examination format. The results of this study showed that the average before chewing pineapple was 1.3 and after chewing pineapple 0.6, so the difference in reduction obtained was 0.7. Based on analysis using the Wilcoxon test, the p value = 0.000 (<0.05). This means that chewing pineapple has the effect of reducing feces.